EFFECT OF SOURSOP LEAF EXTRACT (ANNONA MURICATA L.) ON FASTING BLOOD GLUCOSE LEVELS IN ALLOXAN-INDUCED RATS - Halim, Shiyang Yang; Huwainan Nisa Nasution (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Soursop plant is one of the herbal plants used by the community to overcome various diseases. Soursop plant utilization is widely used for the leaves only. One of the benefits of soursop leaves is to reduce blood glucose levels. This is because soursop leaves contain flavonoids, tannins, and alkaloid compounds. Flavonoid compounds have hypoglycemic effects and act like insulin. Tannin compounds can activate enzymes to facilitate glucose entry into cells and alkaloid compounds can regenerate pancreatic beta cells. This study aims to evaluate the hypoglycemic effect of soursop leaf extract on rats that have been induced by alloxan. This study is a pretest-posttest experimental study with control group design. The study was conducted on white male Wistar rats given soursop leaf extract at a dose of 400mg/KgBW and 800mg/KgBW for 5 days. The analysis test used was One-Way ANOVA. From the research conducted shows that there is a significant relationship between the administration of soursop leaf extract on fasting blood glucose levels in the intervention group with the administration of soursop leaf extract at a dose of 400mg/KgBW and 800mg/KgBW with a value of p = 0.000 in rats induced alloxan with the mean difference in fasting blood glucose levels in the K + group with P1 and P2 is 61.143mg/dL and 82.000mg/dL.